Expansion of Lymphocytes from Prostatic Adenocarcinoma and Adjacent Nonmalignant Tissue - Linh T. Nguyen; Charlotte S. Lo; Michael Fyrsta; Jessica Nie; Jennifer Y. Yam; Pei-Hua Yen; Michael X. Le; Karen Hersey; Miran Kenk; Megan Crumbaker; Neil Fleshner; Girish Kulkarni; et al. (Prostate Cancer)
Background. The evaluation of tumour-infiltrating lymphocytes (TILs) in solid malignancies has yielded insights into immune regulation within the tumour microenvironment and has also led to the development and optimisation of adoptive T cell therapies. Objectives. This study examined the in vitro expansion of TILs from prostate adenocarcinoma, as a preliminary step to evaluate the potential of TILs for adoptive T cell therapy. Design, Setting, and Participants. Malignant and adjacent nonmalignant tissues were obtained from fifteen men undergoing radical prostatectomy. Interventions. There were no study interventions. Outcome Measurements and Statistical Analysis. Expanded cells were analysed by flow cytometry, and the data was assessed for associations between cell subpopulations and expansion rate. Results. Tumour-infiltrating lymphocytes could be expanded to numbers that would be needed to generate a therapeutic infusion product from nine of 15 malignant specimens (60%). The CD4+ T cells predominated over CD8+ T cells (median 56.8% CD4+, 30.0% CD8+), and furthermore, faster TIL expansion was associated with a higher proportion of CD4+ T cells (median 69.8% in faster-growing cultures; 36.8% in slower-growing cultures). A higher proportion of CD3−CD56+ cells versus CD3+ cells was associated with slower TIL expansion in cultures from malignant specimens (median 13.3% in slower-growing cultures versus 2.05% in faster-growing cultures), but not from nonmalignant specimens. Conclusions. The expansion of TILs for potential therapeutic use is feasible. Our findings also indicate that further examination of TILs from prostate adenocarcinomas may yield insights into mechanisms of regulation of T cells within the tumour microenvironment. Further research is required to evaluate their therapeutic potential.